(untitled) (American Journal of Environment and Climate, 2022)
Since the 1960s, inadequate electricity generation has been the bane of economic developments in Nigeria. The introduction of reforms and policies in the electricity sector, for the purposes of exploring renewable energy in electricity generation, is yet to bring about increased electricity generation. This paper examines the challenges of renewable electricity in Nigeria from the regulatory perspective. Studies have shown that the failure of Nigeria to have a regulator specifically for renewable energy is closely linked with the history of electricity generation in Nigeria. Till date, Nigeria does not have a regulator with specific mandates for the development of renewable energy even though there are many regulators with overlap of functions over the development of renewable electricity. Moreover, the power of the Nigerian Electricity Regulatory Commission over the promotion of renewable energy is limited to renewable technologies of certain capacities. This paper will analyse the history of electricity generation in Nigeria in the context of the law and the policy to ascertain how the country has approached the development of renewable energy for electricity generation. The aim is to identify regulatory impediments to the development of renewable electricity from the law and the policy in Nigeria. Recommendations will be made for the establishment of a renewable electricity regulator independent of the existing bodies